The Canadian Muslim Network Tribute to Civil Liberties in Canada: In Honour of Maher Arar and Monia Mazigh: Statement Delivered on behalf of the Canadian Muslim Network by Dr Tyseer Aboulnast, O.ONT, Parliament Hill, Feb 14, 2007 (American Journal of Islam and Society, 2007)
The Honourable Mr Stephane Dion, Leader of the Liberal party of Canada,M. Gilles Duceppe, chef de la Parti Bloc Quebecois, The Honourable JackLayton, Leader of the NDP party, senators and parliamentarians, Mr. Ararand Dr. Mazigh, honored guests, or in likely more appropriate terms for thisevent, friends and fellow Canadians:Assalamu Alaykum. May you all be in Peace.Let me welcome you all with the greeting of Islam on behalf of theCanadian Muslim network; a network of Muslim organizations acrossCanada from BC to Alberta all the way to Ontario, Quebec and the Maritimes.The network was put in place to create an environment of collaborationand communication between Muslim organizations on issues of interestto Muslim Canadians nationally as well as to enhance communication andcollaboration between Canadians of Muslim faith with Canadians of all otherfaiths.The list of names of the organizations in the network is at the back ofyour program (attached here as appendix), and I invite you to look at it indetail to appreciate the breadth of representation here tonight. This initiativeis also supported by a multitude of other organizations that are also listed atthe back.As you may expect civil liberties is high on our agenda. The CanadianMuslim Network is proud to have organized this incredible event to pay tributeto our cherished civil liberties in Canada, to recognize the massive effortthat many in this room exerted to ensure we restore our civil liberties and protectthem for the future of our children and to remind ourselves that while wehave reasons to celebrate our recent successes, the road ahead is still long.We are here today to pay tribute to civil liberties in Canada. Canada is acountry that was never defined by the colour of the skin of its people or theirreligion, rather Canada was always a country defined by its values. Canada ...